Metode Simple Additive Weighting Dalam Seleksi Penerimaan Beasiswa Pada Sekolah Madrasah Ibtidaiyah Al Huda Jakarta Timur - Muhammad Rifki Ramadhan; Arya Nandian Respati; Bakri Syamsah; Anna Mukhayaroh (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2021)
Educational institutions, especially Madrasah Ibtidaiyah, many scholarships are offered to prospective students, scholarships are also given to prospective students at Madrasah Ibtidaiyah Al Huda, East Jakarta, namely in the form of superior scholarships, several problems that often occur, for example the selection process is not accurate due to the large number of applicants who must register. according to the existing criteria, so that the selection process requires accuracy and time so this is not effective. Decision support applications are a way of dealing with the problem of determining scholarships at the Madrasah Ibtidaiyah. This application uses Simple Additive Weighing (SAW), chosen because this method determines the weight of each predetermined criterion then proceeds with the normalization process and continues with the ranking process to select the best alternative. The results of this study are a decision support system in the classification of scholarship recipients using the Simple Additive Weighting (SAW) method at Madrasah Ibtidaiyah Al Huda, East Jakarta based on a website with the results of the selected criteria C1 Academic Achievement, C2 Non-Academic Achievement, C3 Report Value, C4 Personality, C5 Parent's Dependent, C6 Parent's Income. Based on the results of research from the application of a decision support system in classifying scholarship recipients using the Simple Additive Weighting (SAW) method, it was successful so that it could be seen which students deserved the scholarship. This application makes it easier for Madrasah Ibtidaiyah in the new student admissions section to determine scholarship recipients according to existing criteria, faster and on target as expected compared to the previous system. Keywords: Decision Support System, Scholarship, Simple Additive Weighting, Student. Abstrak Lembaga pendidikan khususnya Madrasah Ibtidaiyah banyak sekali beasiswa yang ditawarkan kepada calon siswa, pemberian beasiswa juga diberikan kepada calon siswa di Madrasah Ibtidaiyah Al Huda Jakarta Timur yaitu berupa beasiswa unggul mulia, beberapa permasalahan yang sering terjadi misal proses seleksi yang tidak akurat karena banyaknya pendaftar yang harus sesuai dengan kriteria yang ada, sehingga proses menyeleksi membutuhkan ketelitian dan waktu maka hal ini tidak efektif. Aplikasi pendukung keputusan merupakan cara menangani masalah penentuan beasiswa di Madrasah Ibtidaiyah tersebut. Aplikasi ini menggunakan Simple Additive Weigthing (SAW), dipilih karena metode ini menentuksn bobot dari setiap kriteria yang telah ditentukan kemudian dilanjutkan dengan proses normalisasi dan dilanjutkan dengan proses perangkingan untuk menyeleksi alternatif terbaik. Hasil penelitian ini berupa sistem penunjang keputusan dalam pengklasifikasian siswa penerima beasiswa dengan metode Simple Additive Weighting (SAW) di Madrasah Ibtidaiyah Al Huda Jakarta Timur berbasis website dengan hasil kriteria yang dipilih C1 Prestasi Akademik, C2 Prestasi Non Akademik, C3 Nilai Raport, C4 Kepribadian, C5 Tanggungan Orang Tua, C6 Pendapatan Orang Tua. Berdasarkan hasil penelitian dari aplikasi sistem penunjang keputusan dalam pengklasifikasian siswa penerima beasiswa dengan metode Simple Additive Weighting (SAW) ini berhasil sehingga dapat diketahui siswa yang layak mendapatkan beasiswa. Aplikasi ini memudahkan Madrasah Ibtidaiyah dibagian penerimaan mahasiswa baru untuk menentukan penerima beasiswa sesuai dengan kriteria yang ada, lebih cepat dan tepat sasaran sesuai yang diharapkan dibandingkan dengan sistem sebelumnya. Kata kunci: Beasiswa, Simple Additive Weighting, Sistem Penunjangan Keputusan, Siswa